CLINICAL PHARMACY: ANALYZING THE PHARMACIST’S ROLE IN HEALTHCARE AND HOW TO IMPROVE PATIENT TREATMENT OUTCOMES - Mahdi B, Alzamanan, Mana; Saeed S, Al Abyah, Abdulrahman; Mohammed, Almuhmidhi, Hussain Mana (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
This article explores the integral role of clinical pharmacists in modern healthcare. It delves into the evolution of pharmacy from a primarily dispensary function to a more dynamic, patient-centered role within multidisciplinary healthcare teams. The article examines how clinical pharmacists contribute to patient care, emphasizing their impact on medication management, patient safety, and overall treatment outcomes. It highlights the importance of collaborative practice models, showcasing how pharmacists work alongside other healthcare professionals to optimize patient care. Additionally, the paper discusses the necessary education and continuous professional development for pharmacists, underscoring the importance of staying abreast of emerging trends and technologies in healthcare. It also addresses the pharmacists’ role in public health, ethical challenges, and legal responsibilities within the pharmacy profession. Finally, the article looks at current challenges and future directions, offering insights into how the role of pharmacists might continue to evolve and influence healthcare outcomes. This comprehensive review aims to provide a deeper understanding of the vital contributions of clinical pharmacists in improving patient care and treatment outcomes.